2017
DOI: 10.1146/annurev-immunol-041015-055459
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of Long Noncoding RNAs

Abstract: The discovery of long noncoding RNAs (lncRNA) has provided a new perspective on gene regulation in diverse biological contexts. lncRNAs are remarkably versatile molecules that interact with RNA, DNA, or proteins to promote or restrain the expression of protein-coding genes. Activation of immune cells is associated with dynamic changes in expression of genes, the products of which combat infectious microorganisms, initiate repair, and resolve inflammatory responses in cells and tissues. Recent evidence indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
364
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(367 citation statements)
references
References 107 publications
(126 reference statements)
2
364
0
1
Order By: Relevance
“…Increasing data suggest that lncRNAs are important regulators of diverse biological processes and that their dysregulation is closely linked to the pathogenesis of human diseases, such as Alzheimer's disease, coronary heart disease, myocardial infarction, and membranous nephropathy . lncRNAs also have an important impact on both innate and acquired immunity . However, their specific biological mechanisms remain largely unknown.…”
Section: Introduction Of Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing data suggest that lncRNAs are important regulators of diverse biological processes and that their dysregulation is closely linked to the pathogenesis of human diseases, such as Alzheimer's disease, coronary heart disease, myocardial infarction, and membranous nephropathy . lncRNAs also have an important impact on both innate and acquired immunity . However, their specific biological mechanisms remain largely unknown.…”
Section: Introduction Of Lncrnasmentioning
confidence: 99%
“…Innate immune responses, which constitute the body's nonspecific first line of defense against bacterial pathogens, mainly involve macrophages, dendritic cells (DCs), and natural killer (NK) cells. Innate immune cells express specific lncRNAs when the body is invaded by pathogens, and lncRNAs may thus play critical roles in regulating host–pathogen interactions and the innate immune response …”
Section: Introduction Of Lncrnasmentioning
confidence: 99%
“…These transcripts mostly regulate the expression of other genes. 8 Another area of research in the pathogenesis of MS involves the weakened function of the bloodbrain barrier (BBB). 7 Furthermore, they participate in the regulation of expansion of various immune cells and directing the active transcriptional processes that govern immune cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…19,[37][38][39][40][41][42][43] lncRNAs can regulate the development of various immune cells, such as B and T lymphocytes, macrophages, and dendritic cells (DCs). 44,45 Recent studies showed that several lncRNAs are especially expressed in cells responsible for the innate and adaptive immune response. [44][45][46] Examples include LncRNA-CD244, lincRNA-Cox2, THRIL, TH2-LCR, and lnc-DC, which have been shown to be expressed in T cells, macrophages, and DCs.…”
mentioning
confidence: 99%
“…44,45 Recent studies showed that several lncRNAs are especially expressed in cells responsible for the innate and adaptive immune response. [44][45][46] Examples include LncRNA-CD244, lincRNA-Cox2, THRIL, TH2-LCR, and lnc-DC, which have been shown to be expressed in T cells, macrophages, and DCs. 45 These lncRNAs regulate the transcription of immune-response genes and the production of related cytokines, such as IFN-c, TNF-a, IL-13, IL-5, IL-4, and IL-12, which have all been implicated in the pathogenesis of a variety of uveitis entities.…”
mentioning
confidence: 99%